Injuries in elite women`s ski jumping: a cohort study following three International Ski Federation (FIS) World Cup seasons from 2017-2018 to 2019-2020 - Rebne Stenseth, O. M.; Fløtlien Barli, S.; Martin, K.; Engebretsen, L. (BMJ Open Sport & Exercise Medicine, 2021)
Objectives To define incidence and injury patterns of International Ski Federation (FIS) World Cup (WC) women ski jumpers over three seasons.